The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1039/c6dt03721f
|View full text |Cite
|
Sign up to set email alerts
|

Copper(i) 5-phenylpyrimidine-2-thiolate complexes showing unique optical properties and high visible light-directed catalytic performance

Abstract: Solvothermal reactions of 5-phenylpyrimidine-2-thiol (5-phpymtH) with equimolar CuBr afforded one hexanuclear cluster [Cu(μ-5-phpymt)] (1) along with a tetranuclear by-product [{(CuBr)(μ-5-phpymtH)}(μ-5-phpymt)] (2). A two dimensional (2D) polymer [Cu(μ-5-phpymt)(μ-Br)] (3) was isolated from the reaction of 5-phpymtH with two equiv. of CuBr. Analogous reactions of 5-phpymtH with one or four equiv. of CuI produced one tetranuclear cluster [{Cu(μ-5-phpymtH)(μ-5-phpymt)}(μ-I)] (4) and one 2D polymer [CuI(μ-I)(μ-5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 66 publications
2
23
0
Order By: Relevance
“…Second, N ‐heterocycle thiols such as pyridine‐2‐thione and pyrimidine‐2‐thione can coordinate at Cu I center in either neutral or anion state, which is beneficial in terms of metal–ligand bifunctional mechanism. Third, we and others have observed that Cu I complexes with N,S‐donor ligands exhibit high catalytic activity towards organic reactions such as C−C and C−N bond formations and photocatalytic activity towards the aerobic oxidative hydroxylation of arylboronic acids . Herein, we report an efficient approach for the acceptorless dehydrogenation of secondary/primary benzylic, allylic and aliphatic alcohols for the first time with Cu I N ‐heterocycle thiolate clusters.…”
Section: Introductionmentioning
confidence: 91%
“…Second, N ‐heterocycle thiols such as pyridine‐2‐thione and pyrimidine‐2‐thione can coordinate at Cu I center in either neutral or anion state, which is beneficial in terms of metal–ligand bifunctional mechanism. Third, we and others have observed that Cu I complexes with N,S‐donor ligands exhibit high catalytic activity towards organic reactions such as C−C and C−N bond formations and photocatalytic activity towards the aerobic oxidative hydroxylation of arylboronic acids . Herein, we report an efficient approach for the acceptorless dehydrogenation of secondary/primary benzylic, allylic and aliphatic alcohols for the first time with Cu I N ‐heterocycle thiolate clusters.…”
Section: Introductionmentioning
confidence: 91%
“…Imidazoline-2-chalcogenone ligands NHCE (NHC = N-heterocyclic carbene, E = S, Se) and their transition-metal complexes play a crucial role in organometallic and coordination chemistry as well as in catalysis. Imidazoline-2-chalcogenone ligands are good σ-donors and weak π-acceptors and can be easily modified using appropriate available NHC precursors to allow fine tuning of steric and electronic properties of the center metal complexes. A series of transition-metal complexes with imidazoline-2-chalcogenone ligands have been synthesized for various applications such as C–C bond formation, ,, borylation of alkynes, biomimetic activity, and hydrogen transfer reaction , in recent years. And the catalytic performance of these catalysts is comparable with those of the efficient metal–NHC complexes for organic transformation. , …”
Section: Introductionmentioning
confidence: 99%
“…Their structures were veried by a comparison of NMR parameters with literature data. 98,99 Performing such checks is generally recommended, especially in instances where the appearance of the identied compounds is difficult to rationalise. Such comparisons are considered to be reliable due to sensitivity of NMR parameters to molecular structures.…”
Section: Analysis Of the Chloramination Reaction Pathwaysmentioning
confidence: 99%